IMPLEMENTASI HOTS DALAM MATERI PAI KELAS 1 SD: REFLEKSI PERKEMBANGAN KOGNITIF ANAK MENURUT JEAN PIAGET - Wahyuni, Sri; Mufidah, Vika Nurul; Kristiawan, Nana; Nurbarkah, Suci Siti (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2025)
This study aims to analyze the implementation of the Higher Order Thinking Skills (HOTS) approach in Islamic Religious Education (PAI) learning for first-grade students at SD Islam Al-Badar, as well as its alignment with children’s cognitive development stages based on Jean Piaget’s theory. The research is driven by the national curriculum’s demand to foster critical thinking from an early age, including in PAI learning, which often remains textual and memorization-based. This descriptive qualitative study employed observation, teacher interviews, and document analysis. The findings indicate that elements of HOTS have begun to be applied through open-ended questions, contextual tasks, and reflective activities. However, the implementation remains limited and depends on teachers' ability to adapt HOTS strategies to students’ developmental characteristics. According to Piaget, children aged 6–7 are in the transition from the preoperational to the concrete operational stage, making concrete and contextual HOTS approaches more effective. The study recommends training for teachers in designing HOTS-based instructional strategies aligned with students’ cognitive development, and the development of thematic, enjoyable, and critical-thinking-oriented PAI modules.